Influência do período de amamentação na prevalência de mordidas cruzadas posteriores, em três grupos de crianças brasileiras - Georgevich, Patrícia Valéria Cunha (2011)
There are evidences that breastfeeding contributes for the prevention of malocclusions. Thus, this study investigated the influence of breastfeeding duration, without utilization of baby bottles, on the prevalence of posterior crossbite in three ethnic groups. The sample included 1,472 Brazilian children from the state of São Paulo, with full deciduous dentition, aged 2 to 6 years, divided in three groups: 1) Caucasian (242 males and 265 females), 2) African-Caucasian (298 males and 263 females); and 3) Asian (202 males and 202 females). With the aid of questionnaires responded by the mothers, the sample was divided in three subgroups according to the duration of breastfeeding: A1 – never or for less than three months, A2 – three to eight months, A3 – nine months or longer. The posterior crossbites were diagnosed by clinical examinations, recording the inversion of occlusal contacts between one or more posterior teeth (deciduous canines and/or molars), in relation to their opposing teeth. The association between posterior crossbite and the duration of breastfeeding was evaluated by the chi-square test, Zar ratio test (p<0.05) and odds ratio (or). The prevalence of posterior crossbite in groups A1, A2 and A3, respectively, revealed the following outcomes: 1) Caucasian – 25.5%, 21.1% and 6.8%; 2) African-Caucasian – 20%, 19.5% and 4.1%; 3) Asian – 16.7%, 4.6% and 2.1%; and 4) total sample – 21.8%, 15.4% and 4.2%. The statistical analyses evidenced that the prevalence of posterior crossbite was significantly higher in subgroup A1 compared to A3 in the three ethnic groups, and in subgroup A2 compared to A3, except in Asians. For the total sample, the following was observed: A1 > A3 (or=6.3), A2 > A3 (or=4.1) and A1>A2 (or=1.5), always with p<0.001. It was concluded that a longer duration of breastfeeding, especially above nine months, is associated with a significant reduction in the prevalence of posterior crossbite in the deciduous dentition, in the three ethnic groups analyzed.